Seasonal UV exposure and vitamin D: association with the dynamics of COVID‐19 transmission in Europe. Issue 1 (4th December 2021) - Mukherjee, Sunanda Biswas; Gorohovski, Alessandro; Merzon, Eugene; Levy, Eliad; Mukherjee, Sumit; Frenkel‐Morgenstern, Milana
Abstract : Several recent studies have demonstrated that low plasma 25(OH) vitamin D levels are associated with the risk of COVID‐19 infection. The primary source of vitamin D production in humans is environmental UV radiation. In many viral respiratory diseases, peak infection rates are observed during winter due to reduced UV exposure and low temperatures. In Europe, the second wave of COVID‐19 began early in the winter of 2020. Investigating the impact of seasonal temperature and UV exposure on COVID‐19 transmission could thus aid in prevention and intervention. As such, we first performed a comprehensive meta‐analysis of all related published literature based on the association between vitamin D and COVID‐19, which supported the hypothesis that the low vitamin D level is a critical risk factor for COVID‐19 infection. Next, to understand the potential impact of seasonal UV and temperature levels on COVID‐19 cases, we analyzed meteorological data and daily COVID‐19 cases per million in the populations of 26 European countries. We observed that low temperature, UV index, and cloud‐free vitamin D UV dose (UVDVF) levels are negatively correlated with COVID‐19 prevalence in Europe. Furthermore, a distributed lag nonlinear model was used to assess the nonlinear delayed effects of individual seasonal factors on COVID‐19 cases. Such analysis highlighted the significantly delayed impact of UVDVF on the cumulative relative risk of COVID‐19 infection. The findings of this study suggest that low UV exposure can affect the required production of vitamin D in the body, which substantially influences the dynamics of COVID‐19 transmission and severity. Abstract : We observed a strong correlation of UV exposure with COVID‐19 incidences for 26 European countries. Exposure–lag–response association analysis revealed that UV exposure had a significant delayed effect on COVID‐19 incidences. Meta‐analysis of vitamin D levels in COVID‐19 suggests that low vitamin D level is a critical risk factor for COVID‐19. In conclusion, low UV exposure could affect the required vitamin D production in the body, which substantially impacts COVID‐19 transmission.